A Study of Sexism in Kate Chopin’s ‘The Story of An Hour’ - Regmi, Diwakar (Lumbini Journal of Language and Literature, 2022)
This paper makes an attempt to explore sexism subtly knitted in Kate Chopin’s The Story of An Hour by applying post-feminist perspectives which not only raises voice against women’s subjugation by patriarchal ideology but also against women’s patriarchal attitude towards women who often ventilate sexist language- the product of masculine tutelage towards women. This paper is to find out why they use such opinionated language at women rather than practicing its fair use. Even their assisting utterance also becomes sympathetic and sexist. It is usually masked under the veil of support and sympathy. Chopin’s assumption of the use of gendered language can be seen in Mrs. Josephine upon Mrs. Mallard of this story. This paper will mainly be based on textual reading, feminist interpretation, and library consultation.